Home to the harbor - McClain, Lee Tobin (McClain, Lee Tobin. Off season., 2021)
"Despite the charms of Pleasant Shores, coming home is a last resort for William Gross. The few happy memories he has here all revolve around Bisky Castleman, and she's still every bit as kind and strong-minded as he remembered. But William is reeling from loss, and seeing Bisky with her daughter is a painful reminder of his mistakes. Between running her family's fishing business and being a single mom, Bisky finds her days are full. Yet there's always been room in her heart for William, her one childhood friend who never teased her about her height or her toughness"--